Mid-arm and epitrochlear lymphadenopathy: a clinico-radiological surprise - Garg, Pankaj Kumar; Jain, Bhupendra Kumar; Rathi, Vinita; Singh, Navjeevan; Mohanty, Debajyoti (The Journal of Infection in Developing Countries, 2011)
An 18-year-old man presented with multiple subcutaneous nodules over the anteromedial aspect of his right lower arm. Based on findings of sonography, histopathology, circulating filarial antigen test, and therapeutic response to diethylcarbazine, a diagnosis of filarial lymphadenopathy affecting mid-arm nodes and epitrochlear lymph nodes was made.